PENERAPAN LEMBAR KERJA BERBASIS PROYEK PADA PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH TAHU UNTUK MENINGKATKAN LITERASI LINGKUNGAN - Khuzaimah, A’isyah Nur Hasan; Sari, Sari; Farida, Ida; Sunarya, Risa Rahmawati (Lantanida Journal, 2026)
Low environmental literacy among students remains a challenge, driven by limited interest in environmental issues and low environmental awareness. This study aimed to implement project-based student worksheets in the production of POCIHU (liquid organic fertilizer from tofu wastewater) and analyze the improvement of students' environmental literacy to analyze the characteristics of the resulting POCIHU. A pre-experimental method with a one-group pretest-posttest design was employed, involving 30 students from the Young Scientific Research Group (KIR) at a high school in Bandung. The project-based student worksheets received an average score of 92, which is categorized as very good. Environmental literacy was assessed through four aspects: content, context, process, and attitude. The results showed a significant improvement in environmental literacy, with average N-Gain scores of 0.73 for content, 0.71 for context, and 0.70 for process, all of which were classified as high. The attitude aspect reached 85%, categorized as very good. In addition, the POCIHU product achieved an average score of 97, indicating very good quality. These results indicate that project-based student worksheets are effective in improving students' environmental literacy.